A Method of UAVs Route Optimization Based on the Structure of the Highway Network. (16th December 2015) - Niu, Shuyun; Zhang, Jisheng; Zhang, Fan; Li, Honghai
Abstract : It is essential for transportation management centers to establish a network of fixed and mobile sensors to collect traffic information of highway network, especially for very important links with frequent traffic events. Emerging Unmanned Aerial Vehicles (UAVs), it is introduced as a mobile sensor to collect road traffic information and its cruise route planning problem is researched based on the highway network physical structure. First, according to existing traffic data, a method used to calculate the link importance degree index is proposed, and the index is used to evaluate the link's information. Second, a multiobjective optimization model is proposed, its aim is to minimize the total cruise time under detecting as many important links as possible and minimize the information value undetected by UAVs, and the fuzzy operator is introduced to the constraint conditions. Finally, a case study is used to demonstrate the feasibility and effectiveness of proposed model about UAVs' route planning.